Capitulation of French troops at Atella (23 July 1496) - Gudmann, Joseph Rafael (Tools of war, 2023)
In this paper, I’ll present the first phase of the Italian Wars, specifically the period between 1494 and 1498. The study focuses on the French troops’ capitulation at Atella, which was a very important event as the war tide started to turn against the French following their victorious campaign through the Italian peninsula. The main source for the study was Mario Sanuto’s work called I diarii (‘Diaries’) – a detailed record of the aforementioned events that allow us to analyse the situation and gain clarity about the military, political, and economic aspects of the French army’s capitulation.